2003
DOI: 10.1177/0886260502250835
|View full text |Cite
|
Sign up to set email alerts
|

The Co-Occurrence of Husband-to-Wife Aggression, Family-of-Origin Aggression, and Child Abuse Potential in a Community Sample

Abstract: Despite considerable research on the effects of husband-to-wife aggression, family-of-origin aggression, and child abuse potential, information is limited regarding the co-occurrence of these three family aggression factors and their impact on specific positive and negative dimensions of parenting. This article examines the separate and additive influences of these family aggression variables on mothers’ and fathers’ parenting in two samples of community families. Co-occurrence rates for husband-to-wife aggres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
77
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 36 publications
11
77
0
3
Order By: Relevance
“…One potential explanation for why paternal IPV perpetration was not a significant predictor of father-child attachment could be that it shared a lot of variance with paternal child abuse and did not contribute enough unique variance to father-child attachment. Past research indicates that parental IPV and child abuse often co-occur (e.g., Appel & Holden, 1998;Margolin, Gordis, Medina, & Oliver, 2003). Similarly, exploratory analysis in the current study revealed that paternal IPV perpetration significantly predicted paternal child abuse.…”
Section: Childhood Victimization To Childhood Attachmentsupporting
confidence: 49%
“…One potential explanation for why paternal IPV perpetration was not a significant predictor of father-child attachment could be that it shared a lot of variance with paternal child abuse and did not contribute enough unique variance to father-child attachment. Past research indicates that parental IPV and child abuse often co-occur (e.g., Appel & Holden, 1998;Margolin, Gordis, Medina, & Oliver, 2003). Similarly, exploratory analysis in the current study revealed that paternal IPV perpetration significantly predicted paternal child abuse.…”
Section: Childhood Victimization To Childhood Attachmentsupporting
confidence: 49%
“…The presence of IPV in the family increases the risk that children will in turn be the direct victims of maltreatment [29][30][31][32][33][34]. Several studies have shown that exposure to both IPV and direct CM has an even more deleterious effect on children's adaptation [16,17,35,36].…”
Section: Consequences For Children Of Being Exposed To Intimate Partnmentioning
confidence: 99%
“…The study found that there were significant differences in family cohesion, the parent/child relationship and child wellbeing between the violence groups. At baseline, those who did not experience any physical violence in their relationship had the best outcomes for all three measures, which corroborates the previous research showing that child well-being, family cohesion and the parent child relationship are adversely affected by physical violence in the caretakers' relationship (Rizo et all, 2011;Ireland & Smith, 2009;Brown & Bzostek, 2003;Silvern et al, 1995;Roustit et al, 2009;Russell, Springer & Greenfield 2010;Graham, Bermann & Seng, 2005;Anda, Block, Felitti, 2003;Kernsmith, 2006;Levendosky & Graham-Bermann, 2000, 2001Margolin, Gordis, Medina & Oliver, 2003). This finding was significant (p<.001), showing that those with no physical violence in a relationship had significantly better family cohesion, parent-child relationship, and child well-being than those with CCV or SV.…”
Section: Baseline Differencessupporting
confidence: 76%
“…High jealousy and doubt in the relationship, as well as maternal depression and substance abuse are all frequently present in CCV and could all have an effect on the parent-child relationship (Levondosky et al, 2009, Margolin, Gordis-Medina & Oliver, 2003Warshaw, Sullivan, & Rivera, 2013;Lovejoy et al, 2000). There is also a high degree of instability and uncertainty with Coercive Control Violence due to the cycle of violence that is a feature of CCV.…”
Section: Baseline Differencesmentioning
confidence: 99%
See 1 more Smart Citation